STRATEGI PEMASARAN MENGGUNAKAN ANALISIS SWOT PADA SURAT KABAR PEKANBARU POS DI KOTA PEKANBARU - Susanti Maya; Wijayanto Gatot; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the internal and external environment of Pekanbaru Pos newspaper to determine the appropriate marketing strategy with Pekanbaru Pos with SWOT analysis. This study uses a descriptive qualitative approach, the data collection techniques used in this study are interviews, observations and questionnaires. The sample in this study amounted to 10 people who came from internal and external companies. Based on the results of the analysis using IFAS and EFAS matrices, SWOT Matrix and SWOT Cartesian Diagram, Pekanbaru Pos newspaper is in quadrant I position and the strategy obtained is SO (Strengths and Opportunities) strategy that uses strengths (Strengths) to take advantage of opportunities (Opportunities) . The implementation of the SO strategy is to expand the distribution area and utilize technology to innovate news with qualified human resources.Keywords: Marketing Strategy, IFAS Matrix, EFAS Matrix, SWOT Matrix.